Electrocatalysis Mechanism and Structure–Activity Relationship of Atomically Dispersed Metal‐Nitrogen‐Carbon Catalysts for Electrocatalytic Reactions. Issue 3 (15th January 2023) - Yuan, Long‐Ji; Sui, Xu‐Lei; Liu, Chang; Zhuo, Yu‐Ling; Li, Qi; Pan, Hui; Wang, Zhen‐Bo
Abstract: Atomically dispersed metal‐nitrogen‐carbon catalysts (M‐N‐C) have been widely used in the field of energy conversion, which has already attracted a huge amount of attention. Due to their unsaturated d‐band electronic structure of the center atoms, M‐N‐C catalysts can be applied in different electrocatalytic reactions by adjusting their own microscopic electronic structures to achieve the optimization of the structure–activity relationship. Consequently, it is of great significance for the revelation of electrocatalytic mechanism and structure–activity relationship of M‐N‐C catalysts. Thus, this review first introduces the relative research methods, including in situ/operando characterization techniques and theoretical calculation methods. Furthermore, clarifying the electrocatalytic mechanism and structure–activity relationship of M‐N‐C catalysts in different electrochemical energy conversion reactions is focused. Moreover, the future research directions are pointed out based on the discussion. This review will provide good guidance to systematically study the catalytic mechanism of single‐atom catalysts and reasonably design the single‐atom catalysts. Abstract : Atomically dispersed metal‐nitrogen‐carbon catalysts (M‐N‐C) have been widely used in the field of energy conversion. Electrocatalytic mechanism and structure–activity relationship play a vital role in the preparations and catalytic performance of M‐N‐C catalysts. In this review, the relative research methods are first introduced. Furthermore, clarifying the electrocatalytic mechanism and structure–activity relationship of M‐N‐C catalysts in different catalytic fields is in focus.